OPINI AUDIT GOING CONCERN : KAJIAN BERDASARKAN MODEK PREDIKSI KEBANGKRUTAN, PERTUMBUHAN PERUSAHAAN, LEVERAGE DAN REPUTASI KANTOR AKUNTAN PUBLIK - Farid Muhamadiyah (Media Riset Akuntansi, Auditing & Informasi, 2011)
Going concern audit opinion is the auditor's opinion regarding the ability of the entity to maintain the viability of their business is one of the important things to consider users of financial statements to make decisions especially berinvestas decisions. This study aimed to examine the effect of bankruptcy prediction models (Altman revised model), growth companies (earnings), leverage and reputation of the public accounting firm of the admission trends going concern audit opinion.The sample used in this study consisted of 32 financial statements of listed manufacturing companies in Indonesia Stock Exchange (IDX) during the period 2007-2010. The sample was selected by using the purposive sampling method. In this research data analysis using SPSS by binary logistic regression analysis to test the hypothesis.From the analysis in this study suggests that the use of bankruptcy prediction model (Altman revised model) positive effect on revenue trends going concern audit opinion, while the company's growth , leverage and reputable CPA firm negatively effect revenue trends going concern audit opinion.